Ecological Footprint-Environmental Regulations Nexus: The Case of the Union for the Mediterranean - Karsili, Huseyin; Erkut, Burak (Mdpi, 2022)
The environmental regulations-ecological footprint nexus is occupying an important space in the current debate of energy economics. As a counter measure to environmental degradation, implementing environmental regulations remains on the agenda of scholars and policymakers alike, but whether these regulations have a reducing impact on the ecological footprint remains open since the literature on the topic, and empirical evidence, remains fragmented and dissimilar. The current approach aimed to investigate this for five member countries of the Union for the Mediterranean with panel data econometric techniques. Panel data from France, Italy, Portugal, Spain, and Turkiye were considered for 1992-2015 and were tested for cross-sectional dependence, unit roots, and cointegration. Panel fixed effect regression estimations were conducted, also with Newey-West and Driscoll-Kraay standard errors. In addition, a country-level analysis was conducted by using fully modified ordinary least squares estimation. The results showed that energy consumption and trade increased the environmental footprint, but for environmental regulations, no conclusive effect was identified. The country-level analysis indicated that there is a divergent situation for environmental regulations among the five member countries, where only one out of five member countries showed a significant negative effect. This new empirical evidence for Union for the Mediterranean member countries highlights the importance of a common regulatory policy framework to combat the negative impacts of environmental degradation.
Keywords: environmental regulations; environment patents; ecological footprint; trade; energy consumption